Effect of sipping method on sensory response to single and multiple sips of vanilla milkshake using temporal-check-all-that-apply - Weerawarna N.R.P M; Godfrey AJR; Ellis A; Hort J (Wiley Periodicals LLC, 2022)
Whether drinking from a cup versus through a straw effects sensory perception is inconclusive, as is whether such differences hold across and within multiple sips. This study aimed to determine if product profiles and product discrimination varied depending on whether a product was sipped from a cup or through a straw. An expert panel (n = 9) investigated differences in temporal profiles of six milkshakes across sipping methods. Temporal discrimination across eight attributes was analyzed on selected time slices, across eight sips using generalized linear model Analysis of Deviance. Sweetness, vanilla, astringency, and liquorice attributes were cited significantly more often sipping through a straw, however sipping from a cup showed more significant attribute discriminations across products. Attribute discrimination was increased across multiple sips compared to sip one. Multiple sip TCATA analysis showed significant effects of sipping method within-sips and over multiple sips emphasizing the effects of sipping method on multiple sip TCATA product discriminations. Practical Applications: Milkshakes are often sold in bottles (enabling consumption either directly from the bottle or from a cup) or as on-the-go packs with a straw. This study showed that the sensory profile of milkshake varied depending on whether sipped from a cup or through a straw. However, often-sensory evaluations of beverages are performed by tasting from a cup. This indicates an important practical consideration in terms of sensory study design regarding evaluating products in the intended consumption format or formats. The findings also highlighted the importance of evaluating product volume (or weight) equivalent to single serving size to capture consumer experience closer to actual consumption occasions, as differences in response to one sip changed across multiple sips.